The Relationship between Erythrocytes and Diabetes Mellitus - Yaqi Wang; Peiyuan Yang; Zhaoli Yan; Zhi Liu; Qiang Ma; Zehong Zhang; Yunxia Wang; Yan Su (Journal of Diabetes Research)
High blood glucose level (hyperglycemia) is a leading indicator of diabetes mellitus (DM). Erythrocytes are the most abundant cells in the circulation and the first to perceive changes in plasma composition. Long-lasting hyperglycemia affects the structure and function of erythrocytes. The detection of erythrocyte-related indicators can provide a valuable reference for the prevention, diagnosis, and treatment of DM and its complications. This paper reviews the normal structure and function of erythrocytes, the changes in erythrocytes in patients with diabetes, and the role of erythrocytes in the development of diabetic complications to provide more indicators for the early prevention of DM complications and to monitor the therapeutic effect of DM.